Minimizing waste using lean manufacturing and ECRS principle in Indonesian furniture industry. Issue 1 (1st January 2019) - Suhardi, Bambang; Anisa, Nur; Laksono, Pringgo Widyo
Abstract: The manufacturing industry is considered as one important sector, which has a significant influence on the economic growth of a country. The increase of fierce competition among products requires the company to satisfy their customers by making high-quality products with competitive prices and at on-time deliveries. This study aims to implement lean manufacturing in one of the furniture companies in Indonesia to minimize waste in the production floor. Value Stream Mapping (VSM) will be used as a tool to identify waste by separating value-added activities and non-value added activities in the production process. A future state map is developed with new and improved processes. Future state map makes the improved process more effective and more efficient. The critical waste found on the production floor in motion. Improvements are made using 5W1H techniques and ECRS principles, two simple tools of kaizen. The workload of operator consideration was also done to avoid bottlenecks and decrease the lead time. The result was quietly remarkable as the lead time decreased by around 4.79% and able to balance the workload received by the operator.